Leadership model and planning strategies in private Catholic colleges during the COVID-19 pandemic - Lorensius Lorensius; Warman Warman; Silpanus Silpanus; Theresia Ping (International Journal of Educational Studies in Social Sciences (IJESSS), 2021)
This paper aims to examine the leadership model and planning strategy of private Catholic colleges during the COVID-19 pandemic in Samarinda City, East Kalimantan, Indonesia. This study adopted a qualitative approach using interviews, observations, and documentation to collect data from 10 lecturers and seven staff as. The collected data were then analyzed descriptively. The results of this study indicate that the leadership model that often appears as a hallmark of private Catholic college leadership during the COVID-19 pandemic is a situational and distributed leadership model, with an emphasis on principles of leadership servant in dealing with changing organizational needs. The planning strategy carried out shows a visionary leadership model, college leaders can rearrange strategies that are adapted to the situation in developing educational programs and improving the quality of the college.